1996
DOI: 10.1071/pp9960527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nppb and Niflumic Acid on Outward K+ and Cl- Currents Across the Plasma Membrane of Wheat Root Protoplasts

Abstract: We have tested the effects of the reported Cl- channel blockers NPPB (5-nitro-2-(3- phenylpropylamino)benzoic acid) and niflumic acid (trifluoromethyl-3-phenylamino-2-nicotinic acid) on the slow-activating K+ (IKK.out) and fast-activating Cl- (IClCl.out) outward rectifying currents across the plasma membrane of wheat root protoplasts. Both compounds display a greater potency against IKK.out(half maximal inhibition (IC50) values of 8.7 μM for NPPB and 5.3 μM for niflumic acid with [K+]o= 10 mM) than against ICl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Reversal potentials were also obtained by subtracting the I-V curves before and after addition of niflumate or DPC in 10 mm external TEACl and assuming that the anion current was the only electrogenic transport inhibited by these compounds. Outward K ϩ channels are blocked by niflumate (Garrill et al, 1996), but in the present experiments TEA ϩ was the only cation in the pipette solution. When the average reversal potential of the net currents (45 Ϯ 12 mV, n ϭ 6) was used the P mal 2Ϫ /P Cl Ϫ is 2.6.…”
Section: Al 3؉ -Activated Inward Current Carried By Malate Effluxmentioning
confidence: 85%
“…Reversal potentials were also obtained by subtracting the I-V curves before and after addition of niflumate or DPC in 10 mm external TEACl and assuming that the anion current was the only electrogenic transport inhibited by these compounds. Outward K ϩ channels are blocked by niflumate (Garrill et al, 1996), but in the present experiments TEA ϩ was the only cation in the pipette solution. When the average reversal potential of the net currents (45 Ϯ 12 mV, n ϭ 6) was used the P mal 2Ϫ /P Cl Ϫ is 2.6.…”
Section: Al 3؉ -Activated Inward Current Carried By Malate Effluxmentioning
confidence: 85%
“…In fact, examples of nonspecific inhibition of plant ion channels by molecules developed to block animal ion channels have already been described. Antagonists of animal L-type Ca2+ channels are potent inhibitors of plant K+-outward rectifiers (Terry et al, 1992;Thomine et al, 1994), and, more recently, anion-channel blockers have been shown to interact with plant K+-outward rectifiers (Garrill et al, 1996). An alternative explanation for the variety of effects of anionchannel blockers is that it reveals the existence of a variety of anion channels exhibiting distinct pharmacological profiles and controlling various developmental responses of the plant.…”
Section: Anion-channel Inhibitionmentioning
confidence: 99%
“…Outward currents (i.e. anion influx) have been reported in cells of the root cortex in wheat (Garrill et al, 1996;Skerrett and Tyerman, 1994) and maize (Piñ eros and Kochian, 2001;Piñ eros et al, 2002), as well as in root epidermal cells in Arabidopsis (Diatloff et al, 2004). Likewise, channels mediating inward currents (i.e.…”
Section: +mentioning
confidence: 99%